If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(x + 3) = 6x + 10 Reorder the terms: -1(3 + x) = 6x + 10 (3 * -1 + x * -1) = 6x + 10 (-3 + -1x) = 6x + 10 Reorder the terms: -3 + -1x = 10 + 6x Solving -3 + -1x = 10 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -3 + -1x + -6x = 10 + 6x + -6x Combine like terms: -1x + -6x = -7x -3 + -7x = 10 + 6x + -6x Combine like terms: 6x + -6x = 0 -3 + -7x = 10 + 0 -3 + -7x = 10 Add '3' to each side of the equation. -3 + 3 + -7x = 10 + 3 Combine like terms: -3 + 3 = 0 0 + -7x = 10 + 3 -7x = 10 + 3 Combine like terms: 10 + 3 = 13 -7x = 13 Divide each side by '-7'. x = -1.857142857 Simplifying x = -1.857142857
| 8t^2+2t-1=0 | | 9=X-4 | | -9x+4(3x+-4)=-8+-5x | | -2y-3=5y+11 | | 34x-45+38=32 | | -7+(-4)= | | (x-1294)/1294=.15 | | x+y-6=0 | | 6+x-5/2=x-7/3 | | ax+4=7x+b | | 10+7x=5x+24 | | y-3=2y+5 | | -5x-18=-13 | | 4x+5=-26 | | 5z^2-3z-2=0 | | -2t^2+6t+2=0 | | 6x^2-54=4x^2+4-24 | | 3x-5(x+2)=-6 | | 36=9y | | 4/35+7/40= | | 3x-12-6x+24-9=0 | | 75r^2-48=0 | | C^2+3c-9=0 | | 3x-12-6x+24=9 | | 3(x+4)+2x=8 | | -x+5=-7 | | w=-1vx+8x+-1y | | 8x-w=vx+y | | -7-1=-22 | | 2(x+3)=5x+23 | | 0=8k+8 | | m^3+10m^2+25m=0 |